Enhancing employee retention in the education sector: The role of training and satisfaction - Ni Kadek Suryani; Gede Santanu; Ni Ketut Karwini (Jurnal Siasat Bisnis, 2023)
Purpose – This paper aims to examine the factors that influence employee retention and turnover in the education business sector. Design/methodology/approach This research was conducted at private university in Bali, Indonesia. This study also include 115 lecturers and academic staff respondents. The data were collected by online questionnaire with a Likert scale of 5 and it was processed through the structural equation modelling-based partial least squares. Findings – This study found that training is positively related with job satisfaction and employee retention, and negatively affects employee turnover. Research limitations – This study is unable to generalize the issue due to the data collection that just from a single university, further studies may expand to cover additional demographics and industries for resulting more helpful and comprehensive results. Practical implications – This study gives practice a crucial contribution as it provides valuable guidance on how universities develop and retain talent. Providing regular training companies can retain employees. Originality/value – This result answers the research hypothesis and stated that the most crucial factor in determining the employees leaving is job satisfaction.